County Statistics File 1 (CO-STAT): (United States) ([Verlag nicht ermittelbar], 1985)
Data gathered from a variety of federal agencies and private organizations are contained in this collection which provides county statistics. Included in CO_STAT 1 are all data for counties published in the 1983 County and City Data Book and the 1982 State and Metropolitan Area Data Book, as well as a number of statistics not previously published. There are several levels of data (e.g., persons, housing units, and local governments). The collection supplies information on the following general areas: agriculture, banking, crime, education, elections, government, households, health, housing, labor, land area, manufactures, money income, personal income, population, poverty, retail trade, service industries, social insurance and human services, savings and loan associations, veterans, vital statistics, wholesale trade, and journey to work. Records are included for each of the fifty states and the District of Columbia as well as 3,137 counties or county equivalents.